2002
DOI: 10.1038/sj.jhh.1001300
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological re-appraisal of the association between blood pressure and blood lead: a meta-analysis

Abstract: Studies on the possible association between blood pressure and blood lead have reached divergent conclusions. In a previous meta-analysis, a doubling of the blood lead concentration was associated with a 1.0/0.6 mm Hg increase in systolic and diastolic blood pressure (BP). This meta-analysis updates the analysis originally performed in 1994. Articles on the association between BP and blood lead were identified from computer searches from January 1980 to February 2001 using the Medical Literature Analysis and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(137 citation statements)
references
References 89 publications
3
126
1
4
Order By: Relevance
“…It is well-known that Pb and Cd are toxic and carcinogenic metals (Nawrot et al, 2002). It has been suggested that Pb has a facilitating role in the carcinogenesis through inhibition of DNA synthesis and repair, oxidative injury and interaction with DNA-binding proteins and tumor suppressor proteins (Inskip et al, 1995;Wijngaarden and Dosemeci, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that Pb and Cd are toxic and carcinogenic metals (Nawrot et al, 2002). It has been suggested that Pb has a facilitating role in the carcinogenesis through inhibition of DNA synthesis and repair, oxidative injury and interaction with DNA-binding proteins and tumor suppressor proteins (Inskip et al, 1995;Wijngaarden and Dosemeci, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of data from animals and humans, Cd in food soon becomes absorbed in the blood, then becomes present in plasma, and later binds to red blood cells [34,35]. Cd is established toxic and carcinogenic metals [36,37]. Cd does not induce direct DNA damage, however it induces increase in reactive oxygen species (ROS) formation, which in turn induce DNA damage and can also interfere with cell signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Lead has an exceptionally long half-life in bone compared to other elements (Aufderheide 1989). The many TEs, As, Cd, cobalt, antimony, and mercury (Hg) can deposit in the bone from respiratory exposure (Oakberg et al 2000). Toxic elements (As, Cd, Hg, and Pb) may deplete glutathione and protein-bound sulfhydryl groups, resulting in the production of reactive oxygen species, such as superoxide anion, hydrogen peroxide, and hydroxyl radical (Goyer 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Toxic elements (Cd, Hg, Ni, Pb, and As) may deplete glutathione and protein-bound sulfhydryl groups, resulting in the production of reactive oxygen species such as superoxide anion, hydrogen peroxide, and hydroxyl radical (Goyer 1996). The intake of trace and TEs may promote RA disorders by increasing oxidative stress (for example, by catalyzing the production of reactive oxygen species or inhibiting their degradation) due to the deficiency of an antioxidant element and by increasing blood pressure levels (Nawrot et al 2002). The deficiency of essential nutrients, lack of homeostatic control, or an excess intake of some TEs causes chronic physiological disorders, such as RA, diabetic mellitus, and cardiovascular disease (Nawrot et al 2002).…”
Section: Introductionmentioning
confidence: 99%